The impact of caries status on supragingival plaque and salivary microbiome in children with mixed dentition: a cross-sectional survey - Xiaoxia Yang; Lidan He; Siqi Yan; Xinyi Chen; Guoying Que (BMC, 2021)
Abstract Background Supragingival plaque and saliva are commonly used for microbiome analysis. Many epidemiological studies have identified deciduous teeth caries as a risk factor for caries development in first permanent molar (FPM); nevertheless, to the best of our knowledge, there are no reports on the effects of deciduous teeth caries on the microbiome of healthy FPM. Additionally, it remains unclear whether saliva can be used instead of supragingival plaque for caries microbial studies. Therefore, we aimed to elucidate this issue, and to characterize and compare the oral microbiome of healthy FPMs in children with different caries statuses and that from children with and without caries in a similar microhabitat, by PacBio sequencing. Currently, few studies have investigated the oral microbiome of children using this technique. Methods Thirty children (aged 7-9 years) with mixed dentition were enrolled; 15 had dental caries, and 15 did not. Supragingival plaques of deciduous molars and maxillary FPMs, and non-stimulating saliva samples were collected. DNA was extracted and the v1-v9 regions of 16S rRNA were amplified. Subsequently, PacBio sequencing and bioinformatic analyses were performed for microbiome identification. Results The microbial alpha diversity of the saliva samples was lower than that of the supragingival plaque (p < 0.05); however, no differences were detected between deciduous teeth and FPMs (p > 0.05). In addition, the alpha and beta diversity of children with and without caries was also similar (p > 0.05). Nonmetric multidimensional scaling and Adonis analyses indicated that the microbial structure of salivary and supragingival plaque samples differ (p < 0.05). Further analysis of deciduous teeth plaque showed that Streptococcus mutans, Propionibacterium acidifaciens, and Veillonella dispar were more abundant in children with caries than in those without (p < 0.05); while in FPMs plaque, Selenomonas noxia was more abundant in healthy children (p < 0.05). No differences in microorganisms abundance were found in the saliva subgroups (p > 0.05). Conclusion We have determined that supragingival plaque was the best candidate for studying carious microbiome. Furthermore, S. mutans, V. dispar, and P. acidifaciens were highly associated with deciduous teeth caries. S. noxia may be associated with the abiding health of FPM; however, this requires additional studies.